Retention Mechanism Based on Linear Solvation Energy Relationships to RP-HPLC: A Review - Tian, M.; Tang, B.; Row, K.H. (Asian Journal of Chemistry, 2012)
Linear solvation energy relationships (LSERs) have been used to correlate many complex chemical and biochemical properties with small sets of descriptors of molecular structure and chemistry. The interactions between solutes and solid sorbents are important factors. These interactions are governed by the nature and accessibility of the chemical sites at the material's surface. Characteristics, such as mobile phase modifiers and the type of stationary phase, have been established to detect the retention factors. The descriptors' properties can change as the environmental conditions varied. Comparing predicted and experimental retention factors suggests that the linear solvation energy relationships formalism is able to reproduce adequately the experimental retention factors of the solutes studied in different experimental conditions and evaluate retention characteristics.